PENINGKATAN EKONOMI KELOMPOK TERNAK DESA MANTIASA MELALUI PEMBUATAN BIOGAS KOTORAN SAPI SEBAGAI ENERGI TERBARUKAN - Maulida, Yusni; Ningsih, Rahmita Budiarti; Hellyward, James; Harahap, Anwar Efendi; Juliantoni, Jepri; Iznillah, Muhammad Luthfi; Arigi, Dylan Haikal; Vebryanti, Vebryanti; Mawaddah, Aidha (Jurnal Abdi Insani, 2025)
The Mantiasa Village independent cattle livestock group is a non-productive livestock group. The Mantiasa Village independent cattle livestock group has 25 Balinese cattle. This livestock group is found in Tinggi Tinggi Barat District, Meranti Islands Regency, Riau Province. This group is a location for breeding and fattening livestock commodities, especially Bali cattle. This very high cattle population is directly proportional to the production of livestock manure in the form of feces and urine. Cattle manure that is not utilized optimally will have implications for unfriendly environmental conditions and the spread of livestock diseases will often occur. Therefore, there is a need for technology to use livestock manure as biogas production by designing a household scale reactor. This service aims to produce appropriate technology through the use of solid and liquid waste from livestock manure as a source of biogas. The parameters observed were the degree of acidity (pH) and the flame test. Biogas observation results show that the initial pH of biogas is 7.2-7.4, while the final pH ranges from 7.9-8.2, which shows that biogas has good quality for bacterial growth. The Mantiasa Village livestock community actively participates in training in making biogas using simple, effective technology so that it can improve the community's economy.